The Assessment of Children with Learning Problems: A Planning Process Involving the Teacher. - Ozer, Mark N. (Journal of Learning Disabilities)
Presents a planning process involving special resource teacher focused on the assessment of children with learning problems. Redefinition of the role of the special resource teacher in increasing teacher's awareness of their own problem-solving experiences with the referred child; Overview of the planning process; Role of diagnostic personnel.